PENERAPAN CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN - Aji Setiawan; S Ritonga Ari Putri; Prans Sintia Diadani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Corporate governance is a system that directs and controls a company with the aim of achieving a balance between corporate authority and accountability to stakeholders. Company performance is the result of management activities within each company. Basically, the implementation of corporate governance is not as easy as understanding its concept. The application and management of Good Corporate Governance (GCG) is a concept that emphasizes the importance of shareholders’ rights to obtain correct, accurate, and timely information. Therefore, both public and private companies should view GCG not merely as an accessory, but as an effort to improve company performance and value. There are still many deviations that arise due to the lack of integrity in company management, leading to non-compliance, misunderstandings, conflicts of roles, and dysfunctions in decision-making processes. One of the driving forces behind the implementation of Good Corporate Governance (GCG) comes from the regulatory aspect, namely through the incorporation of basic GCG principles into regulations. GCG emphasizes the protection of shareholders, especially minority shareholders. These interests have basically been accommodated by Law Number 40 of 2007 concerning Limited Liability Companies; however, it cannot be considered perfect, as the presence of the Audit Committee and the Nomination or Remuneration Committee indicates a lag behind current business developments. This study aims to explain the application and implementation of good corporate governance in relation to company performance. The benefits of implementing corporate governance include improving company performance, facilitating access to financing, and restoring investor confidence. This research was conducted through a literature review by collecting relevant journals and books related to the implementation of corporate governance and its impact on company performance.